Curiosity saved the cat: socio-emotional skills mediate the relationship between parental support and career exploration - Gamboa, Vítor; Rodrigues, Suzi; Bértolo, Filipa; Marcelo, Beatriz; Paixão, Olímpio (Frontiers in Psychology, 2023)
According to career literature, greater parental support seems to be associated with higher levels of career exploration. This relationship may be mediated by self-regulatory processes, such as social-emotional skills, as curiosity. However, despite the large number of empirical studies that analyze the antecedents of career exploration, there are no references, to our knowledge, to the role of socio-emotional skills. Following this gap, the present study aims to examine the extent to which perceived parental support is associated with career exploration through the mediating effect of curiosity (socio-emotional skill), among a group of 8th and 9th grade students from public schools in southern Portugal (N=540). An integrated model was conducted using AMOS 20.0 and the results revealed that curiosity is a partial mediator of the relationship between perceived parental support and career exploration. These results highlight the importance of considering socio-emotional skills (such as curiosity) when designing interventions to foster adaptive career behaviors. Theoretical and practical implications are discussed to open the opportunity to progressively extend the participation of proximal contexts (e.g., families) to career and socio-emotional skills development processes.